Relação entre a favela e o lixo: uma ação transformadora - Esgolmin, Luiza Maria (2010)
The aim of this study was to examine how the actions of an intervention on disposal and management of household waste, and the experiences shared during this intervention can facilitate (or hinder) the transformation of values and environmental behavior of individuals in a social community and environmentally vulnerable. In terms of methodological procedures, the research used the qualitative method of research in choosing the technique of action research. The choice fell on the vulnerable community located in a slum area east of the capital of São Paulo has the characteristic of disposing of household waste improperly, usually dumping in the alleys and lanes of the slum, or playing down the hill. The intervention lasted for eight months and was conducted by a team of about twenty indviduals, acting at different stages of intervention. The data were obtained by literature review, participatory observation and interviews with waste pickers and other project participants. The results revealed that the intervention has brought about changes both in behavior and values of community residents. Furthermore, it was found that: (1) individual characteristics and community interventions that were most influenced the participation and appreciation of individual and collective contributions, (2) during the intervention over the shared experiences for a change of behavior and values were participating in seminars, meetings and training wheels and reflection, and interaction among residents provided by the waste collection door to door. However, we observed that the challenge of the problems caused by waste is a management issue that involves not only shared each of the individuas, but also the community as a whole and the government has a key role in ensuring the continuity of actions.